2006
DOI: 10.1016/j.molbiopara.2006.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Differential var gene transcription in Plasmodium falciparum isolates from patients with cerebral malaria compared to hyperparasitaemia

Abstract: The Plasmodium falciparum variant erythrocyte surface antigens known as PfEMP1, encoded by the var gene family, are thought to play a crucial role in malaria pathogenesis because they mediate adhesion to host cells and immuno-modulation. Var genes have been divided into three major groups (A, B and C) and two intermediate groups (B/A and B/C) on the basis of their genomic location and upstream sequence. We analysed expressed sequence tags of the var gene DBLα domain to investigate var gene transcription in rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
180
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(203 citation statements)
references
References 49 publications
17
180
1
1
Order By: Relevance
“…However, this would not explain the actual mechanism of disease onset, because many children with high cys2 levels did not have severe malaria. One possibility, suggested previously (19) is that many children with nonsevere malaria and high cys2 var expression would go on to get severe malaria if not treated. An alternative possibility is that high cys2 var expression merely increases the probability of an event that triggers the onset of severe malaria.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, this would not explain the actual mechanism of disease onset, because many children with high cys2 levels did not have severe malaria. One possibility, suggested previously (19) is that many children with nonsevere malaria and high cys2 var expression would go on to get severe malaria if not treated. An alternative possibility is that high cys2 var expression merely increases the probability of an event that triggers the onset of severe malaria.…”
Section: Discussionmentioning
confidence: 99%
“…In a small pilot study of 12 isolates, children with poorly developed immune responses tended to express cys2 var genes with MFK motifs (16). More recently, Kyriacou et al showed that cys2 var genes were the dominant sequence type expressed by parasites isolated from children with cerebral malaria in Mali (19). These studies support the usefulness of a sequencing approach to comparing PfEMP1 expression between clinical parasite isolates.…”
mentioning
confidence: 88%
See 2 more Smart Citations
“…Se ha observado un incremento significativo en la expresión de transcriptos del grupo B en niños con malaria sintomática (moderada y grave) en Papúa, Nueva Guinea (26,29), Tanzania (28) y Mali (27), mientras los transcriptos de genes C se expresan de forma predominante en los casos de malaria asintomática e hiperparasitemias no asociadas con el desarrollo de manifestaciones graves (26,27,29). Se sugiere la participación de proteínas codificadas por genes de tipo A en el desarrollo de paludismo complicado; dominios DBL-1 del grupo A se han asociado con enfermedad grave y falla multiorgánica en pacientes de Brasil (30 (27,29). Sin embargo, en Papúa no se encontró relación entre enfermedad grave y expresión de genes var A, ni con la formación de rosetas (26,29).…”
Section: Otros Receptores Endotelialesunclassified